Undang-Undang Perkawinan dan Penyuluh Agama dalam Meminimalisir Pernikahan Dini di Indonesia: Law on Marriage and Religious Counselors in Minimizing Early Marriage in Indonesia - Hafas, Imam; Umam, Khoirul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Marriage is an obligation for all muslims, but in the laws and regulations of marriage has a minimum limit to the age. Where this study will discuss about the rise of early marriage in Indonesia along with the factors and implications as well as the role of institutions related to early marriage. This research using the method of phenomenology with normative juridical approach and the data that comes from sources related institutions. The results of this study are expected to be an evaluation material of the parties related to the rise of early marriage in Indonesia, especially in remote areas.